Experiments and Results on the Use of Ontologies in the Artificial Intelligence Domain - Vasile-Daniel Pavaloaia (CES Working Papers, 2012)
The field of agent-based systems as part of the Artificial Intelligence domain is, now-a-days, quite popular. There are specialized technologies required for building software agents and it should be communicative, capable, autonomous and adaptive. In fact, these are the key characteristics required to help make the Internet activity more successful. The limiting factors in building such systems are being overcome, and new approaches are emerging from information technology research laboratories around the world. The use of ontology has proven to be essential elements in many applications and thus, they have been successfully applied in agent systems technology, knowledge management systems, and e-commerce platforms. The current research aims to present besides some theoretical aspects and examples of using the web agents for two European cities.
Keywords: M15; M29; 330; Ontologies; Knowledge Acquisition Systems; Artificial Intelligence; Knowledge management; intelligent agents Romania